Thathiq Lalaran Tashrifan ka Wasilat Ta'līm 'Ilmu al Sharfi fi Ma'had al īmam al Damanhūriy - Inayatul Husnah; Mirel Imelda Sasella; Achmad Diny Hidayatullah (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
Application of  "Lalaran Tasrif" as a learning method for morphology at the Imam Damanhuri Islamic Boarding School Lalaran is one method that can be used to make learning easier. Lalaran means students' memorization technique to memorize certain texts or sentences from the book being studied. The purpose of the research held is to present a solution in overcoming problems to students, especially in studying tools such as nahwu and shorof. This research uses a descriptive qualitative research with the method used are interview and observation. For the result of this research, the application of lalaran is very helpful in the learning process by memorizing so that it is not easy to forget for a long time. In this way, there is no need to memorize continuously, but simply by reading a series of nadzom or wazan which is sung together every day at lalaran time